DIYL (do it yourself laboratories): Inovasi kit perubahan iklim untuk membentuk perilaku BROWNIS (bring your own and eat wisely) pada siswa sekolah menengah pertama - Amani, Shafira Rizka; Kaniawati, Ida; Riandi, Riandi (Assimilation: Indonesian Journal of Biology Education, 2021)
The purposes of this article were to offer the idea of use a climate change kit to learning to form good habits that slowly encourage the formation of environmentally friendly behaviors to reduce the increasingly high rate of global warming. Formal education is a strategic sector that can be used to socialize global warming issues. Including suitable learning tools in global warming material is the right step to provide an understanding of global warming to students in science subjects. The most concrete experiences are direct learning experiences of students. To provide hands-on experience, students can be given science teaching aids. the unity of these props is put together and packed into one container so that the props can be called a kit. There have been many studies on learning tools, various kinds of research have stated that the use of teaching aids has a positive impact on learning. The method used is a literature study. The theme of the SDGs used in the research is climate change action which is goal number 13 (climate action). The output of this idea is the formation of behavior that cares for the environment through understanding the concept of global warming which is learned using a climate change kit.